Neural network modelling of phenolic content, antioxidant capacity and microbial population dynamics of a household scale spontaneous fermentation of Carica papaya leaf / Nor Afiqah Latip ... [et al.] - Latip, Nor Afiqah; So'aib, Mohamad Sufian; Huey, Ling Tan; Senin, Syahrul Fithry; Hamid, Aminuddin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
Beneficial effects of spontaneous fermentation on Carica papaya leaf (CPL) have been observed in terms of enhanced total phenolic content and antioxidant capacity, as well as cultivation of lactic acid bacteria (LAB). Nonetheless, these responses were nonlinear, thus Artificial Neural network (ANN) was used as a predictive tool. The chosen ANN architecture consisted of multi-layer perceptron (MLP) with 2-7-7-1 and 2-10-10-1 topologies, Levenberg-Marquardt training algorithm, and hyperbolic tangent sigmoid activation function.